Oxidative Stress Biomarkers and Early Brain Activity in Extremely Preterm Infants: A Prospective Cohort Study - Caterina Coviello; Serafina Perrone; Giuseppe Buonocore; Simona Negro; Mariangela Longini; Floris Groenendaal; Daniel C. Vijlbrief; Carlo Dani; Manon J. N. L. Benders; Maria Luisa Tataranno (MDPI AG, 2022)
Early brain activity, measured using amplitude-integrated EEG (aEEG), is correlated with neurodevelopmental outcome in preterm newborns. F2-isoprostanes (IPs) are early biomarkers predictive for brain damage. We aimed to investigate the relationship between perinatal IPs concentrations and quantitative aEEG measures in preterm newborns. Thirty-nine infants (gestational age (GA) 24-27 ± 6 weeks) who underwent neuromonitoring using aEEG during the first two days after birth were enrolled. The rate of spontaneous activity transients per minute (SAT rate) and inter-SAT interval (ISI) in seconds were computed. Two postnatal time-points were examined: within 12 h (day 1) and between 24 and 48 h (day 2). IPs were measured in plasma from cord blood (cb-IPs) and between 24 and 48 h (pl-IPs). Multivariable regression analyses were performed to assess the correlation between IPs and brain activity. Cb-IPs were not associated with SAT rate and ISI at day 1. Higher pl-IPs were followed by longer ISI (R = 0.68; p = 0.034) and decreased SAT rate (R = 0.58; p = 0.007) at day 2 after adjusting for GA, FiO2 and IVH. Higher pl-IPs levels are associated with decreased functional brain activity. Thus, pl-IPs may represent a useful biomarker of brain vulnerability in high-risk infants.